2009 IEEE International Conference on Fuzzy Systems 2009
DOI: 10.1109/fuzzy.2009.5277175
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of service management system design of RT-service

Abstract: In this research, we propose the service management system design of robot technology (RT) Service for Interactive Human-Space Design and Intelligence to make robot provide appropriate services according to situations. For this, we propose to define that "Service" as an order that the end user requests and "Task" as elements that compose "Service". We focus on the development of the system that manages services for various robots to work by cooperating. And we systematize RAC (Robot Action Command) for service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In this research, we used Kukanchi Framework as the reference 3D space, shown in Figure 1. This framework was developed in our laboratory from 2007, focusing on sensing technology to construct environmental information using sensor networks and RT Middleware for integrating robots and sensors [10, 11, 12]. Significant work has been done to develop a user interface, system database and Middleware, as well as realizing the functional interaction between human and robot.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we used Kukanchi Framework as the reference 3D space, shown in Figure 1. This framework was developed in our laboratory from 2007, focusing on sensing technology to construct environmental information using sensor networks and RT Middleware for integrating robots and sensors [10, 11, 12]. Significant work has been done to develop a user interface, system database and Middleware, as well as realizing the functional interaction between human and robot.…”
Section: Introductionmentioning
confidence: 99%